ENHANCING INDONESIA'S FOREIGN EXCHANGE EARNINGS THROUGH COLLABORATIVE EFFORTS IN THE INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) INITIATIVE - Natasya Agustiani Saputri; Agung Permadi (Budi Luhur Journal of Strategic & Global Studies, 2025)
Abstract: This research aims to explain the Indonesian government's efforts to develop Indonesian halal tourism through trilateral cooperation with Malaysia and Thailand, known as the Indonesia, Malaysia, Thailand Growth Triangle (IMT-GT), which is cooperation between subregions. To analyze this problem, conceptually this research uses a liberalism paradigm to examine efforts to develop Indonesian halal tourism through IMT GT collaboration carried out by the Indonesian State and Indonesian religious representatives. In improving the country's positive image, Indonesia carries out public diplomacy through halal tourism. In the IMT GT collaboration, halal tourism was proposed because it saw potential through the increasing interest of world Muslim tourists. This type of research is qualitative research using secondary data based on the results of literature studies with the concept of Nation Branding. The Indonesian Nation Branding concept uses halal tourism instruments to make Indonesia a world halal tourist destination and increase foreign tourist visits. One form of Indonesia's Nation Branding is by establishing the Halal Tourism Indonesia Logo, Halal Tourism Indonesia: The Halal Wonders, to describe its halal tourist destinations. Apart from that, other efforts made by Indonesia in diplomacy with halal tourism are through national and international exhibitions. The results of this research also show the efforts of the Indonesian government in developing Indonesian halal tourism through IMT GT collaboration by providing Islamic services and facilities that are more guaranteed halal and comfortable for foreign Muslim tourists visiting Indonesia and also increasing the number of Indonesian halal tourism business actors to improve Indonesia's image. This was done so that the global community, especially the Muslim community, could get to know Indonesia better from Islamic aspects and natural beauty, this succeeded in achieving the strategic plan of the Indonesian government, especially the Ministry of Tourism, through efforts to develop Indonesian halal tourism together with contributions from 2 other countries towards the progress of the tourism industry and factors that will complicate the progress of tourism in IMT-GT members countries if implemented individually. Abstrak: Penelitian ini bertujuan untuk menjelaskan bagaimana upaya pemerintah Indonesia melakukan pengembangan wisata halal melalui kerjasama trilateral bersama Malaysia dan Thailand yang dikenal dengan Indonesia, Malaysia, Thailand Growth Triangle (IMT-GT) yang merupakan kerjasama antar kawasan subregional. Untuk menganalisis permasalah tersebut, secara konseptual penelitian ini menggunakan paradigma liberalisme guna mengkaji upaya pengembangan wisata halal Indonesia melalui kerjasama IMT GT yang dilaksanakan oleh Negara Indonesia serta para perwakilan keagamaan Indonesia. Dalam meningkatkan citra positif negara, Indonesia melakukan diplomasi publik melalui wisata halal. Kerjasama IMT GT mengusung wisata halal karena melihat adanya potensi melalui minat wisatawan muslim dunia yang semakin bertambah. Jenis penelitian ini adalah penelitian kualitatif menggunakan data sekunder berdasarkan hasil studi pustaka. Konsep Nation Branding digunakan sebagai instrument untuk menganalisis pariwisata halal menjadikan Indonesia sebagai destinasi wisata halal dunia dan meningkatkan kunjungan wisatawan mancanegara. Salah satu bentuk Nation Branding Indonesia adalah dengan menetapkan Logo Halal Tourism Indonesia, Halal Tourism Indonesia: The Halal Wonders, untuk menggambarkan destinasi wisata halalnya. Selain itu, upaya lain yang dilakukan Indonesia dalam berdiplomasi dengan pariwisata halal yaitu melalui pameran nasional dan internasional. Hasil kajian dari penelitian ini juga menunjukkan upaya dari pemerintah Indonesia dalam pengembangan wisata halal Indonesia melalui kerjasama IMT GT dengan menyediakan layanan serta fasilitas islami yang lebih terjamin kehalalannya serta kenyamanan bagi para wisatawan muslim mancanegara yang berkunjung ke Indonesia dan juga memperbanyak pelaku usaha wisata halal Indonesia untuk meningkatkan citra Indonesia. Hal tersebut dilakukan sehingga membuat masyarakat global khususnya muslim lebih dapat mengenal Indonesia dari aspek keislaman serta keindahan alam, hal tersebut berhasil mencapai rencana strategi dari pemerintah Indonesia khususnya Kementerian pariwisata melalui upaya pengembangan Wisata halal Indonesia bersama kontribusi dari 2 negara lainnya terhadap kemajuan industri pariwisata serta faktor-faktor yang akan mempersulit kemajuan pariwisata di negara anggota IMT-GT jika dilaksanakan secara sendiri-sendiri.